2023
DOI: 10.1155/2023/7363412
|View full text |Cite
|
Sign up to set email alerts
|

Do Temporomandibular Disorder Patients with Joint Pain Exhibit Forward Head Posture? A Cephalometric Study

Abstract: Purpose. To evaluate head and cervical posture in individuals with or without temporomandibular disorders (TMDs) and to assess the correlations between pain, severity of symptoms, and posture. Methods. A total of 384 patients (129 males and 255 females) was included. The Fonseca Anamnestic Index (FAI) was used to assess the severity and prevalence of TMD and the presence of temporomandibular joint (TMJ) pain. Patients were divided into three groups: the TMD-free group, TMD without TMJ pain group, and TMD with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Yao et al [23] showed signi cant correlation of forward head posture and TMDs. Also, Xiao et al [25] found that TMD patients had a more forward head posture than those without TMD. The results of the above-mentioned studies were all in agreement with the present ndings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yao et al [23] showed signi cant correlation of forward head posture and TMDs. Also, Xiao et al [25] found that TMD patients had a more forward head posture than those without TMD. The results of the above-mentioned studies were all in agreement with the present ndings.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort, Kang [24] reported that in both males and females, neck disability can serve as an initiation point for TMDs. Xiao et al [25] indicated a signi cant correlation between forward head posture and severity of TMDs particularly in males while Inal [26] demonstrated that 78.9% of engineers with a sedentary work had mild to severe TMDs, and pain severity at rest and during activity and neck disability were signi cantly correlated in females. Difference between their results and the present ndings be due to different study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the cranio-mandibular-cervical complex has been considered as an anatomical and functional unit, with neuromuscular restoring forces stabilizing this unit against the force of gravity [81,82]. Epidemiological, clinical, and imaging studies have revealed a significant association between TMJD and neck pain [83][84][85][86]. It is postulated that this association might be due to the convergent nociceptive input from the TMJ and neck structures onto the subnucleuscaudalis in the brain stem [87].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies explore the relationship between disease classi cation and cervical posture. For example, FHP in severe TMD patients was more signi cant compared to mild TMD patients [14]. Moreover, TMD with or without disk reduction signi cantly in uenced the craniocervical posture and hyoid bone position [11,15].…”
mentioning
confidence: 94%